Hole Concentration in GdBaSrCu3-xZnxO7-δ System: Interplay among Superconductivity, Stripe Order and Pseudogap - Chong, Tet Vui; Liow, Chiew Han; Chuah, Suan Cheng; Kambe, Shiro; Roslan, Abd Shukor (INTI International University, 2019)
Polycrystalline GdBaSrCu3O7-δ samples with Zn substitution were prepared via solid state reaction. The superconducting properties of Zn substituted GdBaSrCu3O7-δ samples have been studied by X-ray diffraction, resistivity, AC susceptibility and oxygen content measurements. Hole concentration of these samples was determined according to the oxygen content measured by iodometric titration method. Zn substitution doesn’t change the tetragonal structure of the sample but reduces both Tc and hole concentration, which is attributed to hole filling by Zn. The non-magnetic Zn2+ substitution have significant effects on the oxygen content and effective Cu valence of these d-wave superconductors. The correlation between calculated hole concentration from oxygen content data and Tc obtained leads to the possibly interplay among the superconducting and stripe correlations in GdBaSrCu3-xZnxO7-δ samples.